2021
DOI: 10.1093/jamia/ocab071
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ perceptions of a machine learning model for the identification of atypical medication orders

Abstract: Objectives The study sought to assess the clinical performance of a machine learning model aiming to identify unusual medication orders. Materials and Methods This prospective study was conducted at CHU Sainte-Justine, Canada, from April to August 2020. An unsupervised machine learning model based on GANomaly and 2 baselines were trained to learn medication order patterns from 10 years of data. Clinical pharmacists dichotomou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The most common reason for exclusion on the second screen was that the article did not evaluate human subjects (37.8%), followed by not including medication use (37.1%). Of these, a total of 22 articles were selected to be discussed in our review 11–32 . Of the included studies, data were primarily derived from an academic hospital (43.5%), were located within the United States (43.5%), were retrospective cohort studies (91.3%), and were published in 2020 or later (65.2%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common reason for exclusion on the second screen was that the article did not evaluate human subjects (37.8%), followed by not including medication use (37.1%). Of these, a total of 22 articles were selected to be discussed in our review 11–32 . Of the included studies, data were primarily derived from an academic hospital (43.5%), were located within the United States (43.5%), were retrospective cohort studies (91.3%), and were published in 2020 or later (65.2%).…”
Section: Resultsmentioning
confidence: 99%
“…They found that certain predictors such as level of prescribed experience, type of medication (e.g., antimicrobials), and transitions of care as important areas of focus, which may help manage workload in understaffed pharmacies. Another study evaluated atypical prescription orders, defined as those that deviate from usual prescription patterns, which may identify orders that may require higher scrutiny 19 . The authors evaluated three different ML models, finding that the accuracy of their model was variable by medical specialty, with surgery and neonatal intensive care having the highest and lowest accuracy, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in which each ME in NICU patients (n = 410) was classified and predicted as appropriate-inappropriate, the F 1 score indicating model performance was found to be 0.13 (Hogue et al, 2021). In our study, in which a total of 5,954 medication orders specifically for the NICU were examined, the prediction performance of the model obtained with patients categorized as ME detected or not detected was found to be much higher (F 1 score: 0.931).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical pharmacy practice, AI-powered systems have demonstrated the potential to aid clinical pharmacists, as previously discussed 18 . The development of AI-powered apps and tools is primarily focused on prescription review 19,20 . Furthermore, the AI platform assists clinical pharmacists in drug counseling, thus reducing costs and medical utilization 21 .…”
Section: Introductionmentioning
confidence: 99%